Polysaccharide Isolated From Tetrastigma hemsleyanum Activates TLR4 in Macrophage Cell Lines and Enhances Immune Responses in OVA-Immunized and LLC-Bearing Mouse Models - Zhou, Fang-mei; Chen, Yu-chi; Jin, Chao-ying; Qian, Chao-dong; Zhu, Bing-qi; Zhou, Ying; Ding, Zhi-shan; Wang, Yi-qi (Frontiers in Pharmacology, 2021)
Tetrastigma hemsleyanum Diels et Gilg is a valuable Chinese medicinal herb with a long history of clinical application. Our previous study isolated and characterized a purified polysaccharide from the aerial part of Tetrastigma hemsleyanum (SYQP) and found it has antipyretic and antitumor effects in mice. Preliminary mechanistic study suggests these effects may be related to the binding of Toll like receptor (TLR4). The objective of this study is to further explore the detailed stimulating characteristics of SYQP on TLR4 signaling pathway and its in vivo immune regulating effect. We use HEK-BLUE hTLR4, mouse and human macrophage cell lines as research tools. In vitro results show SYQP activated HEK-BLUE hTLR4 instead of HEK-BLUE Null cells. The secretion and the mRNA expression of cytokines related to TLR4 signaling significantly increased after SYQP treatment in both PMA-induced THP-1 and Raw264.7 macrophage cell lines. The TLR4 antagonist TAK-242 can almost completely abolish this activation. Furthermore, molecules such as IRAK1, NF-κB, MAPKs and IRF-3 in both the MyD88 and TRIF branches were all activated without pathway selection. In vivo results show SYQP enhanced antigen-specific spleen lymphocyte proliferation and serum IgG levels in OVA-immunized C57BL/6 mice. Orally administered 200 mg/kg SYQP induced obvious tumor regression, spleen weight increase and the up-regulation of the mRNA expression of TLR4 related cytokines in Lewis lung carcinoma-bearing mice. These results indicate SYQP can act as both a human and mouse TLR4 agonist and enhance immune responses in mice (p < 0.05). This study provides a basis for the development and utilization of SYQP as a new type of TLR4 agonist in the future.